Estimasi time reproduction number penyebaran awal COVID-19 di Nusa Tenggara Timur, Indonesia - Atti, Astri (Jambura Journal of Biomathematics (JJBM), 2022)
COVID-19 has become a threat to human life. Since the beginning of its spread, the number of deaths due to COVID-19 has reached millions of people and has spread throughout the world including East Nusa Tenggara. To understand the dynamics of the spread of COVID-19 is to use a mathematical model and the indicator used to measure the level of spread is the reproduction number. In this paper, the estimation of the reproduction number (time reproduction number) is carried out using the Extended Kalman Filter (EkF) technique. The data used is daily data for COVID-19 patients from August to October 2021. The estimation results show that the reproduction number of COVID-19 at the beginning of its spread is above one. This means that COVID-19 is spreading in the population.